A Osseointegration in Rabbit Model Using PEEK Coated by HA: Comparative Study for Histological and X-ray - Marwa J. Mohammed; Sadiq J. Hamandi; Marwan N. Arbilei (Newinera Publisher, 2022)
Biocompatible implants are often proposed to improve osseointegration such as metal, polymer, and ceramic to increase bone growth. This study aimed to create a new interface to enhance osseointegration. This interface is between the polymeric part and bone tissue. In this work coat PEEK (polyether ether ketone) plastic material coated with an active biocompatible material (hydroxyapatite). Regarding biocompatibility, coated PEEK was implanted inside the specimen in rabbit bone, the specimens were X-rayed after a period, and a histological investigation was performed after the samples were extracted from the test animals. X-ray and histological examination results indicate increased bone formation in the HA-coated implant compared with the non-coated HA implant.